MtDNA single macrodeletions associated with myopathies: absence of haplogroup-related increased risk - Goios, A (2005)
As for any non-recombining genome, any mutation at mtDNA, if not recurrent, appears on a particular haplotype background, allowing its detection by haplogroup association studies. It has been shown that the propensity for occurrence of single macrodeletions at a level beyond the pathological threshold is associated with super-haplogroup U/K. However, in this report, we present evidence for the absence of preferential haplogroup backgrounds for single macrodeletions. We have analysed how haplogroup diagnostic polymorphisms could disrupt direct repeats usually flanking the deleted segment, and we have concluded that for the Common Deletion, no such polymorphisms are observed in humans, but they do occur in other primates. Furthermore, we also report five new single macrodeletions.